Philosophical foundations of education - Ozmon, Howard; Craver, Samuel M. (Upper Saddle River, N.J. Pearson/Merrill Prentice Hall, 2008)
[This text] provides balanced treatment of all the major schools of thought about education. The authors address how philosophical ideas about education developed over time--arranging their coverage in chronological order--and pay close attention to historical context, while emphasizing each philosophy's continuing relevance to education today. For each philosophy, they show its application in aims, curriculum, methods, and teaching. Additionally, they critically assess each philosophy, and examine how numerous other scholars view it. [It] offers a greater emphasis on women and minorities such as Montessori, De Beauvoir, Greene, DeBois, King, and West. -http://www.booksintprin.com
Idealism and education -- Realism and education -- Eastern philosophy, religion, and education -- Pragmatism and education -- Reconstructionism and education -- Behaviorism and education -- Existentialism, phenomenology, and education -- Analytic philosophy and education -- Marxism and education -- Philosophy, education, and the challenge of postmodernism -- Postscript -- Useful websites and Internet links.
Keywords: Education -- Philosophy -- History; Education -- Aims and objectives; Education -- Study and teaching